Pharmacokinetics, bioavailability and tissue residues of doxycycline in Japanese quails (Coturnix coturnix japonica) after oral administration - Tekeli, Ibrahim Ozan; Turk, Erdinc; Durna Corum, Duygu; Corum, Orhan; Kirgiz, Fatma Ceren; Uney, Kamil (Informa UK Limited, 2020)
This study aimed to determine the bioavailability, tissue residue and withdrawal time of doxycycline after oral administration in Japanese quails (Coturnix coturnix japonica). Japanese quails received doxycycline at 20 mg/kg dose following either single intravenous or oral administration, or 5-day oral administration. Doxycycline concentrations in plasma, liver, kidney, muscle, and skin + fat were determined using high-performance liquid chromatography-ultraviolet. The Withdrawal Time v1.4 software was used to calculate withdrawal times. Following single oral administration, terminal elimination half-life, area under the concentration–time curve from 0 to infinitive time, peak plasma concentration (Cmax) and time to reach Cmax were 10.98 h, 215.84 (h*µg)/mL, 15.33 μg/mL, and 2 h, respectively. The oral bioavailability was 25.84% in quails. In this study, the mean doxycycline concentration was below the maximum residue limit (MRL) at day 4 in skin + fat (0.120 µg/g), and at day 5 in kidney (0.41 µg/g), liver (0.26 µg/g), and muscle (<0.05 µg/g lowest limit of quantification). The highest concentrations of doxycycline after 5-day oral administration were found in kidney compared with other tissues and plasma. These results indicate that the withdrawal times required for doxycycline to reach concentrations
Keywords: Ultraviolet Rays; Administration, Oral; Biological Availability; Coturnix; Japan; Doxycycline; Animals; Tissue Distribution; Chromatography, High Pressure Liquid; 3. Good health